Development, Characterization, and Optimization of Protein Level in Date Bars Using Response Surface Methodology - Muhammad Nadeem; Salim-ur-Rehman; Faqir Muhammad Anjum; Mian Anjum Murtaza; Ghulam Mueen-ud-Din (The Scientific World Journal)
This project was designed to produce a nourishing date bar with commercial value especially for school going children to meet their body development requirements. Protein level of date bars was optimized using response surface methodology (RSM). Economical and underutilized sources, that is, whey protein concentrate and vetch protein isolates, were explored for protein supplementation. Fourteen date bar treatments were produced using a central composite design (CCD) with 2 variables and 3 levels for each variable. Date bars were then analyzed for nutritional profile. Proximate composition revealed that addition of whey protein concentrate and vetch protein isolates improved the nutritional profile of date bars. Protein level, texture, and taste were considerably improved by incorporating 6.05% whey protein concentrate and 4.35% vetch protein isolates in date bar without affecting any sensory characteristics during storage. Response surface methodology was observed as an economical and effective tool to optimize the ingredient level and to discriminate the interactive effects of independent variables.